(untitled) (Journal of Informatics Education and Research, 2025)
This systematic literature review investigates research on Compulsive Buying Behavior (CBB), focusing on an underrepresented consumer group. Utilizing the Scientific Procedures and Rationales for Systematic Literature Reviews (SPAR-4-SLR) protocol and the Theories, Contexts, Characteristics, and Methods (TCCM) framework, 57 articles from the Scopus databases were meticulously analyzed based on predefined keywords and inclusion/exclusion criteria. The review elucidates significant advancements in understanding the theories of CBB, including the Theory of Compulsive Buying Behavior, the Big Five Model, and the Impulsive Buying and Obsessive–Compulsive Buying Theory.